Environmental contamination by batik wastewater and the potential application of activated carbon from pineapple waste for wastewater treatment - Subki, Noor Syuhadah (2017)
The growth of the Malaysian batik industry from its early beginning in the 1930s till now has become a viable local industry. However, batik industries produce a large amount of highly polluted discharge water into the environment which required an extensive treatment. This study was aimed to determine the heavy metal contaminant from batik factory wastewater to the surrounding area. Three different types of samples (batik wastewater, soil and plant) were collected from three different batik factories in Kota Bharu, Kelantan, Peninsular Malaysia. Cadmium (Cd), lead (Pb), zinc (Zn), copper (Cu), chromium (Cr) and iron (Fe) were chosen for the study of heavy metal contaminants. Heavy metal concentrations were detected using Flame Atomic Absorption Spectrophotometer (FAAS). The physicochemical properties of the batik wastewater were also analysed in situ using the YSI Multiprobe parameter. The results indicated that heavy metal concentration in the batik wastewater, soil and plants did not exceed the critical limits set by international and national regulatory authorities. However, heavy metals, typically Cr and Cu are very toxic to human and aquatic life at relatively low concentrations, requiring extensive treatment for batik wastewater before it is discharged into the environment. In this study, activated carbon derived from different pineapple waste was use to remove contaminants such as heavy metals in batik wastewater and also to reduce the abundance of waste generated from the massive production of pineapple in Malaysia. These activated carbons were used to identify the suitability to reduce heavy metals and chemicaloxygen demand (COD) levels in the batik wastewater. The use of activated carbon derived from pineapple crown, peel and core indicated maximum adsorptions of heavy metals of 86.05%, 76.73% and 77.05%, respectively. The comparison between zinc chloride (ZnCl2) and potassium hydroxide (KOH) showed that the pineapple crown activated carbon by KOH activation gave better adsorption value. Capability of activated carbon (KOH) to reduce COD in the batik wastewater showed reduction percentage between 69.23% and 89.87%. This study showed potential of agriculture waste as value added product such as an activated carbon to solve the environmental problems and also helps to solve over abundance pineapple waste altogether.